2022
DOI: 10.1364/oe.460079
|View full text |Cite
|
Sign up to set email alerts
|

Towards retrieving dispersion profiles using quantum-mimic optical coherence tomography and machine learning

Abstract: Artefacts in quantum-mimic optical coherence tomography are considered detrimental because they scramble the images even for the simplest objects. They are a side effect of autocorrelation, which is used in the quantum entanglement mimicking algorithm behind this method. Interestingly, the autocorrelation imprints certain characteristics onto an artefact – it makes its shape and characteristics depend on the amount of dispersion exhibited by the layer that artefact corresponds to. In our method, a neural netwo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…We cast this problem as a Machine Learning problem with an FFT stack as an input and a dispersion profile as an output. Our neural network is based on a modified VGG-16 architecture 17 which we showed is capable of interpreting layer-specific behaviour and output a depth-resolved dispersion profile of the objects 16 . In the modified architecture, batch normalization is added after each convolutional layer and residual blocks are used to sum up the outputs of the pooling layer and convolutional layers.…”
Section: Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…We cast this problem as a Machine Learning problem with an FFT stack as an input and a dispersion profile as an output. Our neural network is based on a modified VGG-16 architecture 17 which we showed is capable of interpreting layer-specific behaviour and output a depth-resolved dispersion profile of the objects 16 . In the modified architecture, batch normalization is added after each convolutional layer and residual blocks are used to sum up the outputs of the pooling layer and convolutional layers.…”
Section: Neural Networkmentioning
confidence: 99%
“…It was shown that Machine Learning 16 - when combined with Qm-OCT - enables to estimate qualitatively GVD value distribution, i.e. a dispersion profile, within an A-scan.…”
Section: Introductionmentioning
confidence: 99%